Corrosion behavior of zirconia in acidulated phosphate fluoride - Anie Thomas; Sathyanarayanan Sridhar; Shant Aghyarian; Pilanda Watkins-curry; Julia Y. Chan; Alessandro Pozzi; Danieli C. Rodrigues (University of São Paulo, 2016)
ABSTRACT Objective The corrosion behavior of zirconia in acidulated phosphate fluoride (APF) representing acidic environments and fluoride treatments was studied. Material and Methods Zirconia rods were immersed in 1.23% and 0.123% APF solutions and maintained at 37°C for determined periods of time. Surfaces of all specimens were imaged using digital microscopy and scanning electron microscopy (SEM). Sample mass and dimensions were measured for mass loss determination. Samples were characterized by powder X-ray diffraction (XRD) to detect changes in crystallinity. A biosensor based on electrochemical impedance spectroscopy (EIS) was used to detect ion dissolution of material into the immersion media. Results Digital microscopy revealed diminishing luster of the materials and SEM showed increased superficial corrosion of zirconia submerged in 1.23% APF. Although no structural change was found, the absorption of salts (sodium phosphate) onto the surface of the materials bathed in 0.123% APF was significant. EIS indicated a greater change of impedance for the immersion solutions with increasing bathing time. Conclusion Immersion of zirconia in APF solutions showed deterioration limited to the surface, not extending to the bulk of the material. Inferences on zirconia performance in acidic oral environment can be elucidated from the study.